1996
DOI: 10.7748/ns1996.10.11.6.33.c2477
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of mechanical aids used within the NHS

Abstract: This paper describes Phase III of the study of mechanical aids used within the NHS, the aim of which was to evaluate the acceptability and effectiveness of mechanical aids within the service. Phases I and II of the study consisted of interviewing nurses and clients concerning their attitudes towards mechanical aids and observing nurses in the clinical area using mechanical aids. Phase III consisted of an experiment being undertaken to compare the usability of a number of mechanical aids for controlled task in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…Given that sling sizing is not standardized across vendors, it is essential that the nurse be familiar with the weight capacity of the particular sling to be used. Moody, McGuire, Hanson, and Tigar (1996) found that 57% of surveyed nurses did not know the maximum weight capacity of the lift, let alone that of the sling. However, nurses must be aware that specified weight limits alone do not predict proper sling fit because the patient's body weight distribution is a significant consideration.…”
Section: Sling Use Guidelinesmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that sling sizing is not standardized across vendors, it is essential that the nurse be familiar with the weight capacity of the particular sling to be used. Moody, McGuire, Hanson, and Tigar (1996) found that 57% of surveyed nurses did not know the maximum weight capacity of the lift, let alone that of the sling. However, nurses must be aware that specified weight limits alone do not predict proper sling fit because the patient's body weight distribution is a significant consideration.…”
Section: Sling Use Guidelinesmentioning
confidence: 99%
“…Sling design has been found to be vital to patient comfort, safety, and dignity (Edlund et al, 1993; McGuire, Moody, & Hanson, 1996). In an evaluation of 10 different lift devices (McGuire, Moody, & Hanson)participants reported that slings providing head and neck support were more comfortable and felt safer than those that did not.…”
Section: Sling Use Guidelinesmentioning
confidence: 99%
“…There is moderate evidence to support the need for improvements with sling design (MDA, 1994;Norton, 2000), position of brakes and handles, mechanisms for raising and lowering, maneuverability (Bell, 1984), and training for proper use of lifts (Olsson & Brandt, 1992). Other issues that need attention are patient dignity and lift instability (Le Bon & Forrester, 1997;McGuire et al, 1996). …”
mentioning
confidence: 99%
“…On the whole, little is known about how patients perceive transfers. Attention to their perceptions is probably essential when developing equipment, methods and policies for patient transfer work, and when developing and evaluating intervention programmes aimed at improving the conditions of these work tasks (McGuire et al 1996a, 1996b, Brown Wilson 2001. Until now, the focus has merely been on preventing musculoskeletal disorders and injuries among health care professionals (Brown Wilson 2001).…”
Section: Issues and Innovations In Nursing Practicementioning
confidence: 99%